Pengaruh Edukasi Pembayaran Pajak; Implementasi e-Samsat dan Program Pemutihan Pajak Kendaraan - Indah Puspitasari; Heni Agustina; Abdussalam Abdussalam; Abu Amar Bustomi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2022)
This study aims to determine the effect of the vehicle tax bleaching program, the implementation of e-samsat, and taxpayer awareness on compliance in paying motor vehicle tax. The number of samples in this study was 100 respondents with a sampling method using the accidental sampling method. Data collection is carried out through questionnaires. The technical data analysis used in this study is multiple linear regression and uses SPSS IMB version 16.0. The results of this study show that the vehicle tax bleaching program and compulsory awareness have a positive and significant effect on taxpayer compliance. Meanwhile, the implementation of e-samsat does not significantly affect taxpayer compliance